2020
DOI: 10.3390/membranes11010008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a New Extracorporeal CO2 Removal Device in an Experimental Setting

Abstract: Background: Ultra-protective lung ventilation in acute respiratory distress syndrome or early weaning and/or avoidance of mechanical ventilation in decompensated chronic obstructive pulmonary disease may be facilitated by the use of extracorporeal CO2 removal (ECCO2R). We tested the CO2 removal performance of a new ECCO2R (CO2RESET) device in an experimental animal model. Methods: Three healthy pigs were mechanically ventilated and connected to the CO2RESET device (surface area = 1.8 m2, EUROSETS S.r.l., Medol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…An experimental study of the CO 2 RESET device (surface area: 1.8 m 2 ; EUROSETS S.R.L., Medolla, Italy) by Nardo et al. revealed that VCO 2 tended to progressively achieve a steady‐state for gas flow rates higher than 2 L/min, while VCO 2 showed an obvious increase with gas flow rate when the rate was below 2 L/min 10 . However, when ECCO 2 R was performed using the ProLung System (surface area 1.8 m 2 ; Estor, Pero, Milan, Italy), VCO 2 was not affected at gas flow rates above 4 L/min 9 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An experimental study of the CO 2 RESET device (surface area: 1.8 m 2 ; EUROSETS S.R.L., Medolla, Italy) by Nardo et al. revealed that VCO 2 tended to progressively achieve a steady‐state for gas flow rates higher than 2 L/min, while VCO 2 showed an obvious increase with gas flow rate when the rate was below 2 L/min 10 . However, when ECCO 2 R was performed using the ProLung System (surface area 1.8 m 2 ; Estor, Pero, Milan, Italy), VCO 2 was not affected at gas flow rates above 4 L/min 9 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in low‐flow venovenous ECLS with large‐size membrane lungs (m 2 ), VCO 2 shows the “ceiling effect”. VCO 2 was not affected by gas flow above 4 L/min in one study, but tended to progressively achieve a steady state for gas flow rates higher than 2 L/min in another; however, these two studies used totally different ECBF platforms 9,10 . Studies showing the variable effects of different combinations of factors are scarce.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, the use of high sweep gas flows, while maximizing the transmembrane gradient, does not increase CO 2 clearance significantly. Indeed, during ECCO 2 R, most of the extracorporeal CO 2 removal capacity is achieved for sweep gas flows below 2 L × min −1 since, at higher flows, the system rapidly loses efficiency [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%